e-Book Development on Chemical Equilibrium Material for Online Learning during Covid-19 Pandemic - Pratiwi Indah Sari; Nina Kadaritna; Emmawaty Sofya (Universitas Lampung, 2021)
Education in Indonesia has changed from offline learning to online learning because of the corona virus. The corona virus has been endemic in Indonesia since early March 2020. The COVID-19 pandemic has changed various aspects of human life, including in the field of education. This condition causes all elements of education to utilize ICT for use in the learning process. One of the uses of ICT can be applied to the development of learning resources. The learning process during the pandemic requires learning resources that are interesting, fun, and in accordance with the applicable curriculum. This research is a type of development research that aims to describe the validity, teacher responses, and student responses to e-books on chemical equilibrium material for online learning during the covid-19 pandemic. The research method used is the Research and Development (RD) method. E-book developed using book creator application. Based on the results of expert validation of the developed e-book, an average percentage of 76.29% was obtained with high criteria in the aspect of content suitability. In the construction aspect of 82.95%, readability of 82.22%, and attractiveness of 83.8%, all three have very high criteria. The results of the teacher's response to the suitability aspect of the material content are 86.67%, readability is 85.6%, and attractiveness is 86.8%, all three have very high criteria. The results of students' responses to the readability aspect were 84.5% and attractiveness was 83.9%, both of which had very high criteria. From the research results it can be stated that the e-book developed is valid.Keywords: e-Book, chemical equilibrium, book creator, covid-19 pandemicDoi: 10.23960/jppk.v10.i3.2021.01